The Coupling of Safety and Security Exploring Interrelations in Theory and Practice - Bieder, Corinne; Pettersen Gould, Kenneth (SpringerBriefs in Applied Sciences and Technology; SpringerBriefs in Safety Management, 2020)
This open access book explores the synergies and tensions between safety and security management from a variety of perspectives and by combining input from numerous disciplines. It defines the concepts of safety and security, and discusses the methodological, organizational and institutional implications that accompany approaching them as separate entities and combining them, respectively. The book explores the coupling of safety and security from different perspectives, especially: the concepts and methods of risk, safety and security; the managerial aspects; user experiences in connection with safety and security. Given its scope, the book will be of interest to researchers and practitioners in the fields of safety and security, and to anyone working at a business or in an industry concerned with how safety and security should be managed.